Multiple Depth DB Tables Indexing on the Sphere - Luciano Nicastro; Giorgio Calderone (Advances in Astronomy)
Any project dealing with large astronomical datasets should consider the use of a relational database server (RDBS). Queries requiring quick selections on sky regions, objects cross-matching and other high-level data investigations involving sky coordinates could be unfeasible if tables are missing an effective indexing scheme. In this paper we present the Dynamic Index Facility (DIF) software package. By using the HTM and HEALPix sky pixelization schema, it allows a very efficient indexing and management of spherical data stored into MySQL tables. Any table hosting spherical coordinates can be automatically managed by DIF using any number of sky resolutions at the same time. DIF comprises a set of facilities among which SQL callable functions to perform queries on circular and rectangular regions. Moreover, by removing the limitations and difficulties of 2-d data indexing, DIF allows the full exploitation of the RDBS capabilities. Performance tests on Giga-entries tables are reported together with some practical usage of the package.